Catalog of the biting midges of Argentina (Diptera: Ceratopogonidae) - Spinelli, Gustavo R.; Ronderos, María M.; Ayala, Mahia M.; Díaz, Florentina (Zootaxa, 2023)
Three hundred and fiftysix species of ceratopogonids in 35 genera are listed for Argentina, with most species in Forcipomyia Meigen (67 species) Culicoides Latreille (51 species), Stilobezzia Kieffer (40 species) and Dasyhelea Kieffer (37 species). For each listed species, the following information is included: sex and/or life stage described in the original description, type locality, type status and sex, depository of type material, distribution, georeferenced localities for Argentina (provinces are underlined) and main references that include the original description and those that specify locations in the country. Specific epithets of synonyms are accompanied by type locality, type status and sex, and location of type material. New localities from Argentina for 102 species are provided, and the following 16 species are newly recorded from the country: Forcipomyia (Caloforcipomyia) glauca Macfie, Forcipomyia (C.) hatoensis Utmar & Wirth, F. (Euprojoannisia) bromeliae Saunders, F. (E.) quasiingrami Macfie, F. (Forcipomyia) zonogaster Ingram & Macfie, F. (F.) catarinensis Marino & Spinelli, F. (Lasiohelea) cornuta Saunders, F. (Metaforcipomyia) osaensis Spinelli, Marino & Borkent, F. (Phytohelea) bromelicola (Lutz), F. (Trichohelea) goniognatha Wirth & Messersmith, F. (T.) leptognatha Wirth & Messersmith, Brachypogon (Brachypogon) woodruffi Spinelli & Grogan, Physohelea turgidipes Ingram & Macfie, Bezzia gibbera (Coquillett), Bezzia schmitzorum Dippolito & Spinelli and Palpomyia versicolor Macfie. Leptoconops brasiliensis (Lutz) and Clastrieromyia dycei Spinelli & Grogan are excluded from the Argentinean fauna.